2015
DOI: 10.1002/jms.3615
|View full text |Cite
|
Sign up to set email alerts
|

Emission of volatile sesquiterpenes and monoterpenes in grapevine genotypes following Plasmopara viticola inoculation in vitro

Abstract: The grapevine (Vitis vinifera) is one of the most widely cultivated fruit crops globally, and one of its most important diseases in terms of economic losses is downy mildew, caused by Plasmopara viticola. Several wild Vitis species have been found to be resistant to this pathogen and have been used in breeding programs to introduce resistance traits to susceptible cultivars. Plant defense is based on different mechanisms, and volatile organic compounds (VOCs) play a major role in the response to insects and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 56 publications
(110 reference statements)
1
24
1
Order By: Relevance
“…Terpenoids induced by herbivores act in plant defense by attracting insect predators, and by acting as repellents or toxic compounds (Turlings and Tumlinson, 1992; Wegener et al, 2001). Besides, they have been associated to resistance against downy mildew in grapevine (Alarcón et al, 2015). However, the role of terpenoids in plant-bacteria interactions is not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids induced by herbivores act in plant defense by attracting insect predators, and by acting as repellents or toxic compounds (Turlings and Tumlinson, 1992; Wegener et al, 2001). Besides, they have been associated to resistance against downy mildew in grapevine (Alarcón et al, 2015). However, the role of terpenoids in plant-bacteria interactions is not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Cabernet Sauvignon) were propagated from wood cuttings in a greenhouse. All tests were performed with fully expanded grapevine leaves from the fourth to sixth leaf positions from the shoot tip on foliar discs [4].…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Grapevine (Vitisvinifera) is one of the major fruit crops worldwide [1]. However, grapevine downy mildew, one of the most destructive diseases caused by Plasmopara viticola (P. viticola) [2], can lead to significant reduction (by 20%-30%) of yield [3][4][5]. Disease management has been one of the major tasks for viticulture after the infection of the plant by downy mildew [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported positive correlations between plant volatile terpenoid emissions and resistance to plant pathogens 57 . For example, downy mildew (Plasmopara viticola )-resistant grapevine genotypes emitted significantly more monoterpenes and sesquiterpenes than susceptible genotypes 58 . Rice genotypes resistant to the bacterial pathogen, Xanthomonas oryzae pv.…”
Section: Discussionmentioning
confidence: 99%